Ethics on Compulsion of Vaccinations in the Age of COVID-19 - Tsuriel Rashi (Dubai Medical Journal)
The COVID-19 pandemic broke out at the end of 2019 and throughout 2020 there were intensive international efforts to find a vaccine for the disease, which has already led to the deaths of a few million people. In December 2020, several pharmaceutical companies announced that they had succeeded in producing effective vaccines and after approval by the various regulatory bodies, countries started to vaccinate their citizens. With the start of the global campaign to vaccinate the world’s population against COVID-19, there was a strong renewal of the debate about the possibility of enforcing vaccination, either directly or indirectly, in particular on account of the rapid spread of the pandemic. This article presents the stand that Jewish ethics takes on this issue. According to the norms of Jewish ethics, a moral person has an obligation toward his fellows and G-d to be vaccinated. Notwithstanding the importance of vaccination, Jewish ethics does not allow direct coercion but recognizes that someone who does not get vaccinated presents a danger to the public and so can be prevented from circulating freely. Thus, Jewish ethics permits indirect compulsion by keeping children and adults who are not vaccinated away from educational institutions and public places, respectively. Only occasionally and in special circumstances would it be permitted to resort to shaming of a person who refuses to be vaccinated and only if he/she is deemed a particular danger to the public health.